Transcultural Collaboration: Epistemic Fluency and Identity - Carr, Anne (2024)
This article explores the development of epistemic skills through transcultural collaborations among students and professors from eight universities across continents. The study emphasizes the importance of dialogue in enhancing critical thinking and epistemic fluency in global contexts. By engaging students in discussions on global migration and epistemic justice, the research highlights the role of dialogic participation in fostering inclusivity and understanding diverse epistemologies. The projects "Epistemic (In)justice" and "Epistemologies of Inclusion across Continents and Cultures" revealed the potential of digital technology to facilitate meaningful intercultural exchanges while also underscoring the need for epistemic fluency to navigate complex global issues. The findings suggest that educational institutions must prioritize the cultivation of both hard and soft skills to prepare students for active, informed participation in a globalized world.